Deficiência e capacitismo: o ensino e a aprendizagem musical a partir de práticas pedagógicas anticapacitistas (Orfeu, 2023)
This text is part of studies for a doc-torate in progress, whose central theme is the inclusion of students with disabil-ities and disorders in the context of mu-sical teaching and learning. The specific objective of this text is to consider the models of understanding disability and raise discussions about ableism, under-standing it as a form of violence. To meet this purpose, the text was prepared in the form of an essay, under the theoretical contribution of authors in the field such as Débora Diniz, Marivete Gesser, Isabel Maior and Juliana Segalla. In the final sec-tion, some examples of pedagogical prac-tices carried out by one of the authors are presented. It is concluded that in order to think about the development of a mu-sical teaching and learning context with anti-capacitance pedagogical practic-es, it is necessary to be willing to build a transforming pedagogy that is based on flexibility, creativity, respect for diversity, the transformation of consciousness and the fight against everyday violence. We believe that thinking about a music class-room with anti-capacitance pedagogical practices involves, above all, being willing to build a transformative pedagogy that is based on respect for diversity.
Keywords: disability; ableism; music teaching and learning; anticapacity pedagogical practices